Update on Osaka University Twin Registry: An Overview of Multidisciplinary Research Resources and Biobank at Osaka University Center for Twin Research. (27th December 2019) - Honda, Chika; Watanabe, Mikio; Tomizawa, Rie; Sakai, Norio
Abstract: The Osaka University Twin Registry was originally established as a registry of older twins but was subsequently expanded to include twins of all ages. The Center for Twin Research at Osaka University Graduate School of Medicine has been managing this registry, as well as collecting research information and bioresources from twin participants. Based on the resources, multidisciplinary research projects have been conducted in collaboration with researchers from institutions both inside and outside Japan. One of the main aims of the center is to collect research information as well as biological resources from registered twins, and to establish a biobank and databases of these data and bioresources. Although data availability may vary, the following data have been collected: physical data (e.g., height, body weight, blood pressure, theoretical visceral fat, pulse wave velocity and bone density); epidemiological data (e.g., medical history, lifestyle, quality of life, mood status, cognitive function and nutritional status); electrocardiography, ultrasonography (carotid artery and thyroid); dentistry, dermatological assessment; positron emission tomography; magnetoencephalographam; brain magnetic resonance imaging (MRI); and functional MRI. In addition to these in-person survey data, microbiome data have been collected from some participants. As for bioresources, peripheral blood is obtained from the participants for isolation of serum and extraction of DNA and RNA, then stored in deep freezers for further analyses. A variety of research projects are in progress and more are on the way both in Japan and internationally using these data.